Case Report: Preventing X-linked retinoschisis transmission via MARSALA-based PGT-M - Li, Jieliang; Wen, Xiaojun; Ou, Zhanhui; Fang, Xiaowu; Du, Jing; Lin, Xiufeng; Ke, Wanna; Wu, Jiaqi; Liu, Nengqing (Frontiers in Ophthalmology, 2026)
X-linked retinoschisis (XLRS) is an X-linked recessive inherited retinal disease caused by mutations in the RS1 gene. This case report describes the successful application of preimplantation genetic testing for monogenic diseases (PGT-M) to prevent the intergenerational transmission of a pathogenic RS1 variant within a family. Prior to PGT-M, the family had a male child with XLRS who experienced bilateral visual impairment and metamorphopsia at 4 years of age. we employed next-generation sequencing (NGS) to identify a single-nucleotide variant, c.187T>C (p. Cys63Arg; NM_000330.4), in RS1. Subsequently, we identified the mutation in the proband and his parents, which was confirmed by Sanger sequencing. In the PGT-M cycle, eight blastocysts were biopsied and analyzed using the “Mutated allele revealed by sequencing with aneuploidy and linkage analyses (MARSALA)” platform. This involved whole-genome amplification via multiple annealing and looping-based amplification cycles (MALBAC), followed by next-generation sequencing for concurrent single-nucleotide polymorphism (SNP) haplotype analysis to track the mutant allele and comprehensive chromosomal copy number variation (CNV) screening. The analysis identified three euploid embryos (E1, E4 and E5) without the familial RS1 mutation. A high-quality embryo (E1, 6AA) was transferred following genetic counseling, resulting in a clinical pregnancy. Mid-trimester amniocentesis confirmed a normal male karyotype and the absence of the pathogenic RS1 variant, leading to the birth of a healthy baby. This case demonstrates that the integrated MARSALA-based PGT-M strategy is a powerful tool for families with X-linked disorders to conceive healthy offspring.